18F PET with florbetapir for the early diagnosis of Alzheimer’s disease dementia and other dementias in people with mild cognitive impairment (MCI) - Martínez, Gabriel (Cochrane Database Syst Rev, 2017)
BACKGROUND: (18)F‐florbetapir uptake by brain tissue measured by positron emission tomography (PET) is accepted by regulatory agencies like the Food and Drug Administration (FDA) and the European Medicine Agencies (EMA) for assessing amyloid load in people with dementia. Its added value is mainly demonstrated by excluding Alzheimer's pathology in an established dementia diagnosis. However, the National Institute on Aging and Alzheimer's Association (NIA‐AA) revised the diagnostic criteria for Alzheimer's disease and confidence in the diagnosis of mild cognitive impairment (MCI) due to Alzheimer's disease may be increased when using amyloid biomarkers tests like (18)F‐florbetapir. These tests, added to the MCI core clinical criteria, might increase the diagnostic test accuracy (DTA) of a testing strategy. However, the DTA of (18)F‐florbetapir to predict the progression from MCI to Alzheimer’s disease dementia (ADD) or other dementias has not yet been systematically evaluated. OBJECTIVES: To determine the DTA of the (18)F‐florbetapir PET scan for detecting people with MCI at time of performing the test who will clinically progress to ADD, other forms of dementia (non‐ADD), or any form of dementia at follow‐up. SEARCH METHODS: This review is current to May 2017. We searched MEDLINE (OvidSP), Embase (OvidSP), PsycINFO (OvidSP), BIOSIS Citation Index (Thomson Reuters Web of Science), Web of Science Core Collection, including the Science Citation Index (Thomson Reuters Web of Science) and the Conference Proceedings Citation Index (Thomson Reuters Web of Science), LILACS (BIREME), CINAHL (EBSCOhost), ClinicalTrials.gov (https://clinicaltrials.gov), and the World Health Organization International Clinical Trials Registry Platform (WHO ICTRP) (http://www.who.int/ictrp/search/en/). We also searched ALOIS, the Cochrane Dementia & Cognitive Improvement Group’s specialised register of dementia studies (http://www.medicine.ox.ac.uk/alois/). We checked the reference lists of any relevant studies and systematic reviews, and performed citation tracking using the Science Citation Index to identify any additional relevant studies. No language or date restrictions were applied to the electronic searches. SELECTION CRITERIA: We included studies that had prospectively defined cohorts with any accepted definition of MCI at time of performing the test and the use of (18)F‐florbetapir scan to evaluate the DTA of the progression from MCI to ADD or other forms of dementia. In addition, we only selected studies that applied a reference standard for Alzheimer’s dementia diagnosis, for example, National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer’s Disease and Related Disorders Association (NINCDS‐ADRDA) or Diagnostic and Statistical Manual of Mental Disorders‐IV (DSM‐IV) criteria. DATA COLLECTION AND ANALYSIS: We screened all titles and abstracts identified in electronic‐database searches. Two review authors independently selected studies for inclusion and extracted data to create two‐by‐two tables, showing the binary test results cross‐classified with the binary reference standard. We used these data to calculate sensitivities, specificities, and their 95% confidence intervals. Two independent assessors performed quality assessment using the QUADAS‐2 tool plus some additional items to assess the methodological quality of the included studies. MAIN RESULTS: We included three studies, two of which evaluated the progression from MCI to ADD, and one evaluated the progression from MCI to any form of dementia. Progression from MCI to ADD was evaluated in 448 participants. The studies reported data on 401 participants with 1.6 years of follow‐up and in 47 participants with three years of follow‐up. Sixty‐one (15.2%) participants converted at 1.6 years follow‐up; nine (19.1%) participants converted at three years of follow‐up. Progression from MCI to any form of dementia was evaluated in five participants with 1.5 years of follow‐up, with three (60%) participants converting to any form of dementia. There were concerns regarding applicability in the reference standard in all three studies. Regarding the domain of flow and timing, two studies were considered at high risk of bias. MCI to ADD; Progression from MCI to ADD in those with a follow‐up between two to less than four years had a sensitivity of 67% (95% CI 30 to 93) and a specificity of 71% (95% CI 54 to 85) by visual assessment (n = 47, 1 study). Progression from MCI to ADD in those with a follow‐up between one to less than two years had a sensitivity of 89% (95% CI 78 to 95) and a specificity of 58% (95% CI 53 to 64) by visual assessment, and a sensitivity of 87% (95% CI 76 to 94) and a specificity of 51% (95% CI 45 to 56) by quantitative assessment by the standardised uptake value ratio (SUVR)(n = 401, 1 study). MCI to any form of dementia; Progression from MCI to any form of dementia in those with a follow‐up between one to less than two years had a sensitivity of 67% (95% CI 9 to 99) and a specificity of 50% (95% CI 1 to 99) by visual assessment (n = 5, 1 study). MCI to any other forms of dementia (non‐ADD); There was no information regarding the progression from MCI to any other form of dementia (non‐ADD). AUTHORS' CONCLUSIONS: Although sensitivity was good in one included study, considering the poor specificity and the limited data available in the literature, we cannot recommend routine use of (18)F‐florbetapir PET in clinical practice to predict the progression from MCI to ADD. Because of the poor sensitivity and specificity, limited number of included participants, and the limited data available in the literature, we cannot recommend its routine use in clinical practice to predict the progression from MCI to any form of dementia. Because of the high financial costs of (18)F‐florbetapir, clearly demonstrating the DTA and standardising the process of this modality are important prior to its wider use.